Prognostic significance of tumor deposit counts in stage III colorectal cancer based on T/N staging and chemotherapy status: A retrospective cohort study - Chenxiao Zheng, MD; Lingsha Xu, MD; Binbin Ou, MD; Ibrahim Mohamed Bakour Abdourahaman, MD; Xuanqin Chen, MD; Hangjia Xu, MD; Yating Zheng, MD; Yifei Pan, MD (Surgery Open Science)
Background: We aimed to evaluate the impact of tumor deposit (TD) count on cancer-specific survival (CSS) and disease-free survival (DFS) in stage III colorectal cancer (CRC) patients stratified by T and N staging, and further explore its impact on chemotherapy effect. Method: We determined the optimal TD cut-off value for stage III CRC patients from the SEER database utilizing X-tile analysis, and retrospectively analyzed the clinicopathological data of 443 patients from the First Affiliated Hospital of Wenzhou Medical University from 2019 to 2020. Chi-square (χ2) tests compared categorical variables. Kaplan–Meier assessed CSS and DFS. Cox regression model evaluated prognostic factors on CSS and DFS. Results: 2TD is the optimal cutoff value for prognosis in Stage III CRC, in the low-risk group (T1-T3 and N1), ≥3TD patients faced higher cancer-specific mortality (HR = 3.445, 95%CI = 1.254–9.465, P = 0.017) and recurrence risks (HR = 1.934, 95%CI = 1.095–3.416, P = 0.024) vs. 1-2TD, while 1-2TD and no-TD patients showed no difference in survival. In the high-risk group (T4 or N2), both ≥3TD and 1-2TD patients had poor prognosis. Chemotherapy reduced cancer-specific mortality in both groups (1-2TD: HR = 0.347, 95%CI = 0.138–0.870, P = 0.024; ≥3TD: HR = 0.272, 95%CI = 0.077–0.960, P = 0.043) but did not significantly improve recurrence risk (1-2TD: P = 0.177; ≥3TD: P = 0.058). Conclusion: TD indicates poor prognosis in stage III CRC, with ≥3 TD significantly worsening survival, yet the prognosis remains poor in TD-positive patients with high-risk (T4 or N2) regardless of TD count. Moreover, TD count does not influence chemotherapy's mortality benefit.